Is Spirituality Included in Spanish Language Pain Assessment Scales? A Scoping Review of Instruments Available - de Diego-Cordero, Rocio; Martin-Palomino, Emilio; Aranda-Jerez, Alicia; Perez-Jimenez, Jose Miguel; Lucchetti, Giancarlo (2025)
The subjective and biopsychosocial-spiritual nature of pain makes its assessment difficult. Although multidimensional scales exist, few pain instruments have included spiritual aspects in their development, so our purpose is to investigate the inclusion of spirituality in pain assessment scales available in Spanish. A review of the scientific literature was carried out in the PubMed, SCOPUS and Web of Science databases. To make the search more exhaustive, Internet databases were searched, and the Spanish Pain Society was consulted. For each instrument, items were rated and classified according to a broader (i.e., family, nature, transcendence, meaning) or narrower (i.e., deity or higher power) definition of spirituality. Out of a total of 838 items searched in the databases, 8 multidimensional pain scales were found in Spanish, and 5 included items related to spirituality and/or religiosity. Most of the scales do not focus directly on the assessment of spiritual pain. Although the Coping with Chronic Pain Questionnaire has clear items related to prayer, God, faith and seeking religious leaders, the other scales only touch on spiritual definitions and most of these would lead to "contaminated" results due to poor design. It seems that these scales were not originally designed to assess the spiritual dimension of pain but, instead, have some existential items that are linked to a broader definition of spirituality, such as hope, suffering, emptiness and meaning. The present review has revealed that most pain scales available in Spanish were not originally designed to investigate spiritual pain, assessing indirectly items related to spirituality. These findings highlight that, although spirituality is an important aspect of pain, its assessment is still scarce in clinical practice and research. Future instruments should include a more holistic view of pain, which includes aspects related to spirituality and religiousness.
Keywords: Grief; Grief dimension; Health professional; Hope; Life course perspective; Spirituality